Noble birth in Sophocles’ plays - Mac Mahon, Seymour Mark (2024)
This dissertation studies the theme of good breeding in five of Sophocles’ extant plays, as well as incorporating a discussion of the relevant fragments. The theme is contextualised against its literary-philosophical as well as political background to better understand Sophocles’ unique stance and his motive for engaging so thoroughly with the theme. The thesis is that Sophocles, with certain qualifications, believes that excellence could be transmitted by heredity, and because the Greek conception of excellence always has a strong socio-political element, the implication in the plays is that those of good breeding, who had been marginalised by the democracy but were capable of providing much benefit, need to be reintegrated into Athenian political society.